Outcome after decompressive craniectomy in older adults after traumatic brain injury - Kapapa, Thomas; Jesuthasan, Stefanie; Schiller, Franziska; Schiller, Frederike; Woischneck, Dieter; Gräve, Stefanie; Barth, Eberhard; Mayer, Benjamin; Oehmichen, Marcel; Pala, Andrej (Frontiers in Medicine, 2024)
Objective: Globally, many societies are experiencing an increase in the number of older adults (> 65 years). However, there has been a widening gap between the chronological and biological age of older adults. The aim of this study was to investigate the outcome after traumatic brain injury (TBI) and decompressive craniectomy (DC) in older adults. A social proportion that trends to a more active and social participating part of the society with an age of >65 years. Methods: A retrospective, multi-centre, descriptive, observational study was used, including patients who were treated between 2005 and 2022. Outcome after discharge and 12 months was evaluated according to the Glasgow Outcome Scale (Sliding dichotomy based on three prognostic bands). Significance was established as p≤0.05. Results: A total of 223 patients were included. The majority (N=158, 70.9%) survived TBI and DC at discharge. However, unfavourable outcome was predominant at discharge (88%) and after 12 months (67%). There was a difference in favour of younger patients (≤65 years) between the age groups at discharge (p=0.006) and at 12 months (p<0.001). A subgroup analysis of the older patients (> 65 years) did not reveal any significant differences. After 12 months, 64% of the older patients had a fatal outcome. Only 10% of those >65 years old had a good or very good outcome. 25% were depending on support in everyday activities. After 12 months, the age (OR 0.937, p=0.007, CI 95%: 0.894 to 0.981; univariate) and performed cranioplasty (univariate and multivariate results) were influential factors for the dichotomized GOS. For unfavourable outcome after 12 months, the thresholds were calculated for age = 55.5 years (p<0.001), time = 8.25 hours (p=0.671) and GCS = 4 (p=0.429). Conclusion: Even under the current modern conditions of neuro-critical care, with significant advances in intensive care and rehabilitation medicine, patients > 65 years of age following severe TBI and DC were rarely independent and usually required significant support. This aspect should also be taken into account during counselling for a very mobile and active older section of society, together with the patient's will.